A small neighborhood well-organized: seasonal and daily activity patterns of the community of large and mid-sized mammals around waterholes in the Gobi Desert, Mongolia - Nasanbat, Battogtokh; Ceacero, Francisco; Ravchig, Samiya (Frontiers in zoology, 2021)
BACKGROUND: Animal communities have complex patterns of ecological segregation at different levels according to food resources, habitats, behavior, and activity patterns. Understanding these patterns among the community is essential for the conservation of the whole ecosystem. However, these networks are difficult to study nowadays, due to anthropic disturbances and local extinctions, making it difficult to conclude if segregation patterns are natural or human-induced. We studied ecological segregation in a community of large and mid-sized mammals in the Great Gobi Desert, a remote arid area free from recent extinctions and human disturbances. Activity patterns of 10 sympatric mammal species were monitored around 6 waterholes through camera-trapping over a two-year period, and analyzed them primarily through circular statistics. RESULTS: Complex patterns of spatial, seasonal, and daily segregation were found. Overlap in seasonal activity was detected in only 3 of the 45 possible pairs of species. Four species used the waterholes all-year-round, while others peaked their activity during different periods. The Bactrian camel showed continuous daily activity, the grey wolf had bimodal activity, and the argali and Siberian ibex were diurnal, while the others had nocturnal peaks during different hours. Daily and spatial overlap were both detected in only 6 of the 45 pairs. Only one species pair (snow leopard and Eurasian lynx) showed an overlap at two levels: seasonal and daily. Climate and moon phase significantly affected the activity of certain species. CONCLUSIONS: Altogether, the results showed complex patterns of ecological segregation at different levels in the use of the key resource in arid environments: waterholes. These results are important for understanding the biology of these species under natural conditions, as well as potential changes in altered ecosystems, and may help to design conservation strategies.
Keywords: Ecological segregation; Camera-trapping; Waterholes; Activity overlap; Arid environments; Resource competition